ANALISIS DAMPAK PERMAINAN MOBA TERHADAP SIKAP MANUSIA MENGGUNAKAN K-MEANS CLUSTERING - Geri Nugraha; Alam Rahmatulloh (Institut Teknologi Nasional Malang, 2025)
In this study, we explore the impact of MOBA games, specifically Mobile Legends and Honor of Kings, on players' attitudes and behaviors. The main focus discussed is the tendency for anger and aggressiveness to emerge during play. The purpose of this study is to understand the relationship between frequency of play and social attitudes and interactions between players. The methods we applied included a survey to collect data, as well as the application of the K-Means Clustering algorithm to group players based on their game characteristics. The results of the analysis showed that 65% of respondents felt less irritable after playing, while 70% reported improved teamwork skills. Visualization of the data through scatter plots, heatmaps, and centroid plots provided clear insights into player behavior patterns and stress levels experienced after playing. Through the application of K-Means Clustering, we found a significant trend between playing frequency and aggressive attitudes, with 55% of frequent players exhibiting high levels of anger. Thus, this study is expected to provide a deeper understanding of how MOBA games affect individual attitudes as well as social interactions among young players.